Genetics of Frontotemporal Lobar Degeneration - Galimberti, Daniela; Scarpini, Elio (Frontiers in Neurology, 2012)
Frontotemporal Lobar Degeneration (FTLD) is the most frequent neurodegenerative disorder with a presenile onset. It presents with a spectrum of clinical manifestations, ranging from behavioural and executive impairment to language disorders and motor dysfunction. Familial aggregation is frequently reported in FTLD, and about 10% of cases have an autosomal dominant transmission. Microtubule Associated Protein Tau gene (MAPT) mutations have been the first ones identified and are generally associated with early onset behavioural variant Frontotemporal Dementia (bvFTD) phenotype. More recently, progranulin gene (GRN) mutations were recognized in association with familial form of FTLD. In addition, other genes are linked to rare cases of familial FTLD. Lastly, a number of genetic risk factors for sporadic forms have also been identified.